2010
DOI: 10.1002/jmor.10835
|View full text |Cite
|
Sign up to set email alerts
|

Exoskeletal chitin scales isometrically with body size in terrestrial insects

Abstract: The skeletal system of animals provides the support for a variety of activities and functions. For animals such as mammals, which have endoskeletons, research has shown that skeletal investment (mass) scales with body mass to the 1.1 power. In this study, we ask how exoskeletal investment in insects scales with body mass. We measured the body mass and mass of exoskeletal chitin of 551 adult terrestrial insects of 245 species, with dry masses ranging from 0.0001 to 2.41 g (0.0002-6.13 g wet mass) to assess the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
57
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 40 publications
3
57
0
Order By: Relevance
“…Investment in structural support may also contribute to an upper size limit for vertebrates, because endoskeleton scales hypermetrically with body mass (Prange et al, 1979), although it probably does not generally do so for insects, because exoskeletal chitin increases isometrically with body mass (M 1 ) (Lease and Wolf, 2010). Two exceptions, interestingly, are Coleoptera and Orthoptera, where exoskeletal chitin scaling is hypermetric (M 1.1 ; statistically distinguishable from M 1 for Coleoptera) (Lease and Wolf, 2010). Regardless of the exoskeleton's potential role in limiting beetle maximal body size, there is a large and growing body of evidence that insect body size is constrained by tracheal oxygen delivery .…”
Section: Discussionmentioning
confidence: 99%
“…Investment in structural support may also contribute to an upper size limit for vertebrates, because endoskeleton scales hypermetrically with body mass (Prange et al, 1979), although it probably does not generally do so for insects, because exoskeletal chitin increases isometrically with body mass (M 1 ) (Lease and Wolf, 2010). Two exceptions, interestingly, are Coleoptera and Orthoptera, where exoskeletal chitin scaling is hypermetric (M 1.1 ; statistically distinguishable from M 1 for Coleoptera) (Lease and Wolf, 2010). Regardless of the exoskeleton's potential role in limiting beetle maximal body size, there is a large and growing body of evidence that insect body size is constrained by tracheal oxygen delivery .…”
Section: Discussionmentioning
confidence: 99%
“…For example, SC models, including DEB theory [85,156] are supported by the positive allometry of fat mass in mammals [17], and of 'dead wood' in plants [28,29], but they are contradicted by the isometry of fat and skeletal tissues in insects [157,197] (see also Section 2.2.1). Furthermore, a study designed to test SC effects showed that hypometric metabolic scaling is not caused by a positive allometry of either fat or exoskeletal materials in 15 species of carabid beetles [198].…”
Section: System-composition Modelsmentioning
confidence: 99%
“…The chitin content in the new cuticle of dsBmorCPR2 individuals (with RNAi phenotype) was significantly lower than that of the control group (dsRed as a control) ( Figure 4G). The process of cuticle extension and increasing of body size require chitin as crude material (Merzendorfer and Zimoch 2003;Lease and Wolf 2010), and therefore simultaneously, larval molting is a critical period for the formation and growth of new cuticles. Accordingly, we propose that suppression of BmorCPR2 decreases the chitin content and level of BmorCPR2, resulting in limitation of remodeling and extension of the larval cuticle and weakened body cavity capacity.…”
Section: Bmorcpr2 Affects Cuticle Chitin Content and Larval Molting Vmentioning
confidence: 99%
“…In procuticles, chitin fibers are arranged in laminae in an antiparallel manner and superimpose each other, forming sheets of fibrils that are stacked in a helicoidal fashion, maintaining cuticle structure, elasticity, and stability (Bouligand 1965;Neville and Luke 1969;Moussian 2010). In terrestrial insects, the chitin content is positively correlated with body size, suggesting a close relationship with cuticle extension and expansion (Merzendorfer and Zimoch 2003;Lease and Wolf 2010).Cuticular proteins (CPs), the principal structural constituents of cuticle, are encoded by more than 100 genes in known insect genomes (Andersen et al 1995 The soft, flexible cuticle of Lepidoptera larvae not only bears pressure from the internal contents on the integument to stabilize the long cylindrical body, but is also conducive to movement and expanding feeding and survival areas (Carter and Locke 1993;Brackenbury 1997;Lin et al 2009). However, the mechanisms by which cuticular proteins participate in body-shape stability and adaptability of Lepidoptera is presently unclear.…”
mentioning
confidence: 99%
See 1 more Smart Citation